2001
DOI: 10.1089/104303401750298562
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfer of Manganese Superoxide Dismutase Reverses Vascular Dysfunction in the Absence But Not in the Presence of Atherosclerotic Plaque

Abstract: Impaired endothelium-dependent vasorelaxation (EDVR) is observed in hypercholesterolemia both in the presence and absence of morphological abnormalities and may be due to superoxide anions. Our aim was to assess the effect of gene transfer of manganese superoxide dismutase (MnSOD) to blood vessels from hypercholesterolemic animals with and without atherosclerotic plaque and to compare the effects of endothelial nitric oxide synthase (eNOS) and MnSOD over-expression on vascular dysfunction in the setting of ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 27 publications
4
15
1
Order By: Relevance
“…However, these findings were in agreement with recent studies that have convincingly demonstrated that ex vivo and in vivo gene transfer of eNOS or neuronal NO synthase restores NO-mediated arterial relaxations that were impaired by increased superoxide production in hypertensive, 29,30 atherosclerotic, [31][32][33][34] or diabetic [35][36][37][38] animals. These experimental observations support the novel concept that NO generated by recombinant NO synthase, as a result of gene transfer, provides an effective means of inactivating superoxide and, thereby, improving vascular function, including endotheliumdependent relaxation, in vessels with elevated superoxide.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, these findings were in agreement with recent studies that have convincingly demonstrated that ex vivo and in vivo gene transfer of eNOS or neuronal NO synthase restores NO-mediated arterial relaxations that were impaired by increased superoxide production in hypertensive, 29,30 atherosclerotic, [31][32][33][34] or diabetic [35][36][37][38] animals. These experimental observations support the novel concept that NO generated by recombinant NO synthase, as a result of gene transfer, provides an effective means of inactivating superoxide and, thereby, improving vascular function, including endotheliumdependent relaxation, in vessels with elevated superoxide.…”
Section: Discussionsupporting
confidence: 92%
“…33 On the other hand, studies from other groups have shown that gene transfer of MnSOD and CuZnSOD normalized such impaired vasomotor function in diabetic vessels 37 and atherosclerotic vessels without plaque formation. 38 On the basis of the different results of these studies, we decided to examine the effect of MnSOD gene transfer, because mitochondria may also be a key source of superoxide production in addition to the cytosol and extracellular space. 13 Our results of MnSOD gene transfer on vascular VCAM-1 and superoxide levels are in agreement with the latter reports.…”
Section: Discussionmentioning
confidence: 99%
“…We chose MnSOD for vascular gene transfer because (1) our recent study indicates that endogenous MnSOD is significantly reduced in the carotid arteries of DOCA-salt hypertensive rats and that gene transfer of MnSOD restored the functional capacity of the antioxidant enzyme in scavenging elevated O 2 Ϫ 9 and (2) mitochondria may be a major location in which vascular O 2 Ϫ is produced. 29 In agreement with our findings, gene transfer of MnSOD has been shown to normalize superoxide-induced impairment of endothelium-dependent relaxation, 30,31 whereas gene transfer of cytosolic Cu/Zn-SOD or extracellular SOD did not. [32][33][34] Conversely, recent studies have demonstrated that both ex vivo and in vivo gene transfer of eNOS or nNOS restored NO-mediated arterial relaxation, which was impaired by increased O 2 Ϫ in hypertensive, 34,35 atherosclerotic, 31,33,36 -38 or diabetic animals.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, AdMnSOD gene transfer has been shown to improve NO-mediated vasorelaxation in models of atherosclerosis and diabetes. 21,42 The apparent discrepancy in results between these findings and ours may be explained by the different disease models used, the larger viral dose used and the probability that a 1-h ex vivo infection is more effective than a 20-min in vivo infection.…”
Section: Discussioncontrasting
confidence: 61%